Site-directed deuteration of dronedarone preserves cytochrome P4502J2 activity and mitigates its cardiac adverse effects in canine arrhythmic hearts - Aneesh V. Karkhanis; Gopalakrishnan Venkatesan; Ryuichi Kambayashi; Jacqueline Wen Hui Leow; Marcus Qingrui Han; Hiroko Izumi-Nakaseko; Ai Goto; Jeremy Kah Sheng Pang; Boon Seng Soh; Pipin Kojodjojo; Atsushi Sugiyama; Eric Chun Yong Chan (Elsevier, 2022)
Cytochrome P4502J2 (CYP2J2) metabolizes arachidonic acid (AA) to cardioprotective epoxyeicosatrienoic acids (EETs). Dronedarone, an antiarrhythmic drug prescribed for treatment of atrial fibrillation (AF) induces cardiac adverse effects (AEs) with poorly understood mechanisms. We previously demonstrated that dronedarone inactivates CYP2J2 potently and irreversibly, disrupts AA-EET pathway leading to cardiac mitochondrial toxicity rescuable via EET enrichment. In this study, we investigated if mitigation of CYP2J2 inhibition prevents dronedarone-induced cardiac AEs. We first synthesized a deuterated analogue of dronedarone (termed poyendarone) and demonstrated that it neither inactivates CYP2J2, disrupts AA-EETs metabolism nor causes cardiac mitochondrial toxicity in vitro. Our patch-clamp experiments demonstrated that pharmacoelectrophysiology of dronedarone is unaffected by deuteration. Next, we show that dronedarone treatment or CYP2J2 knockdown in spontaneously beating cardiomyocytes indicative of depleted CYP2J2 activity exacerbates beat-to-beat (BTB) variability reflective of proarrhythmic phenotype. In contrast, poyendarone treatment yields significantly lower BTB variability compared to dronedarone in cardiomyocytes indicative of preserved CYP2J2 activity. Importantly, poyendarone and dronedarone display similar antiarrhythmic properties in the canine model of persistent AF, while poyendarone substantially reduces beat-to-beat variability of repolarization duration suggestive of diminished proarrhythmic risk. Our findings prove that deuteration of dronedarone prevents CYP2J2 inactivation and mitigates dronedarone-induced cardiac AEs.